Identification of Pyrotechnic Shock Sources for Shear Type Explosive Bolt - Yanhua Li; Shihui Xiong; Yuan Li; Xiaogang Li; Yuquan Wen; Huina Mu; Zhiliang Li (Shock and Vibration)
To identify the shock generated sources of shear type explosive bolt, five kinds of explosive bolts with different states, including high preload, low preload, no preload, no piston shear, and only propellant combustion, were designed. The decoupling of four kinds of shock sources, including the collision of propellant combustion, piston shear weak surface, end of piston stroke, and preload release, was realized. Their acceleration responses at 15 cm from the shock source center on 60 cm × 60 cm × 1 cm equivalent aluminum plate were measured by using the piezoresistive accelerometer. On this account, the relative contribution values along with frequency and the mean relative values without regard to frequency of various sources were calculated in high and low preload. Results show that the characteristics of different shock sources are different, and the shock induced by propellant combustion is mainly caused by high frequency, while piston shear and piston impact are concentrated in medium and low frequency. In the high preload condition, the preload release is major contributor to the overall shock response output, accounting for approximately 57.51%, while the contributions of the three shock sources of propellant combustion, piston shear, and piston impact are equivalent, but they are significant contributors in the low preload condition. This study provides design reference to reduce the pyrotechnic shock of shear type explosive bolt.